2020
DOI: 10.1186/s13104-020-05125-y
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value of red cell distribution width for stroke severity and outcome

Abstract: Objectives: In the present study, we sought to investigate the association between red cell distribution width (RDW) and stroke severity and outcome in patients who underwent anti-thrombolytic therapy with tissue plasminogen activator (tPA). Results: In this prospective study, 282 stroke patients who underwent tPA injection were included. The categorization of RDW to < 12.9% and > 13% values revealed insignificant difference in stroke severity score, accounting for the mean 36-h NIHSS of 8.19 ± 8.2 in normal R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…These finding suggest that differences in outcome between patients receiving thrombolytic therapy may be related to the severity of stroke at ED admission. By contrast, Shahsavarinia et al [ 25 ] reported that the baseline RDW did not correlate with outcome after a 3-month follow-up in patients who received tPA treatment. Ye et al [ 26 ] found that RDW was not associated with clinical outcome after 1 year but was significantly related to all-cause mortality.…”
Section: Discussionmentioning
confidence: 96%
“…These finding suggest that differences in outcome between patients receiving thrombolytic therapy may be related to the severity of stroke at ED admission. By contrast, Shahsavarinia et al [ 25 ] reported that the baseline RDW did not correlate with outcome after a 3-month follow-up in patients who received tPA treatment. Ye et al [ 26 ] found that RDW was not associated with clinical outcome after 1 year but was significantly related to all-cause mortality.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, our present results also showed the differences of between mean RDW levels at different time points of peripheral thrombolysis period and the occurrence of favorable outcome and all cause death were not found. This was supported by the study of Kavous Shahsavarinia [46]. They found that no significant difference in mRS between those with normal and higher RDW values either in the 36 h, 7 day or in 3-month.…”
Section: Discussionmentioning
confidence: 65%
“…However, Shahsavarinia et al concluded that RDW is not a significant predictive value for either stroke severity or stroke outcome in patients after tPA administration. They suggested that this may be due to the narrowing of the patient pool, and this negative result should be analyzed to understand the underlying mechanism ( 36 ).…”
Section: Discussionmentioning
confidence: 99%